Credit risk management and financial performance: A study of listed Banks in Sri Lanka - Asvini, N.; Pamila, S. (University of Jaffna, 2020)
This study tends to explore the credit risk management and financial performance of listed banks in Sri Lanka over the period from 2015 to 2019 by using Non-Performing Loan Ratio (NPLR) and Equity to Total Assets Ratio (ETAR) as credit risk management indicators and Return on Assets (ROA) and Return on Equity (ROE) as indicators of financial performance. This study considers all 13 banks listed in Sri Lanka, and the secondary data is collected via annual reports of respective banks. For empirical analysis, this study uses descriptive analysis, correlation, and multiple regression analysis. The results from regression analysis confirmed that credit risk management has a significant impact on banks' financial performance. While correlation analysis revealed that equity to total assets ratio is significantly positively correlated with return on asset and significantly negatively correlated with return on equity while non-performing loan ratio reveals an insignificant relationship. These insights are helpful for academic understanding and policy formulation by the decision-makers of the bank.
Keywords: credit risk management; financial performance; listed banks; Sri Lanka